(untitled) (International Journal of Applied Research in Management and Economics, 2020)
Children today are very comfortable using electronic technology, Internet, on line games and digital platforms. The dominant portion of the on line content is consumed via their parent’s technological devices. Knowing that children are not able to recognize media content from intentional advertising, raises the complex question of whether and how Internet advertising can be regulated and how children can be protected. The negative implications of children’s exposure to on line advertising can be categorized in: financial and psychological, and are summarized but not limited to: obesity, anxiety paired with influence over domestic spending’s, psychological and ethical issues. This raises the complex question of whether and how Internet advertising can be regulated and how children can be protected from the negative implications. The majority of research are focused on institutional regulations and industrial limitations but the importance and the role of the parents as a regularity mechanism is underestimated. The theory recognizes that certain parental style differs on how they view online exposure of their children and that influence their role in the process on regulation children exposure on online advertising. From the other side digital literacy of the parents is very important milestone in the proses positioning the parents in a role of as a self-regulation mechanism of children exposure. The industry and the regulators should be alerted for this matter in all parts of the world, since this issue is rising negative implication.